The Development of Adopting Innovation on Entrepreneurship Status of Madura Cattle Farmers - R. Pambudy (Tropical Animal Science Journal, 2018)
Developing of Madura cattle should be focused on the base of Madura cattle, that is able to scale up farmers’ profits. Expansion obstacle of livestock sub-sector closely related by adopting innovation. Farmers require entrepreneurship skills in responding to technology development. This research aimed to analyze factors affecting adopting innovation steps and how the adoption can be influenced in forming entrepreneurship status of Madura cattle farmers. This research was conducted in Madura Island. The data used is primary data obtained from respondents of 92 farmers of Madura cattle. The data were analyzed descriptively and quantitatively using PLS-SEM analytical tools. The research showed that characteristics of entrepreneurs and communication process affected adopting innovation of Madura cattle farmers. Adopting innovation is able to be affected on shaping entrepreneurship status of Madura cattle farmers namely socially responsible entrepreneurs.